Experimental Investigations of Backfill Conditions on the Performance of High-Density Polyethelene Pipes - Terzi, N. U.; Yilmazturk, F.; Yildirim, S.; Kilic, H. (WILEY-BLACKWELL, 2012)
In this study, a series of laboratory tests on 100-mm-diameter high-density polyethylene (HDPE) 100 PE flexible pipe buried in poorly graded Sile quartz sand with different relative densities are described. The laboratory tests were performed in a 40-mm-thick plexiglass fronted test tank that replicated a classical trench section in field conditions. The HDPE flexible pipe was positioned against the glass with its longitudinal axis perpendicular to the glass. This allowed direct observation of the backfillpipe interactions. Three high-definition photogrammetric cameras were used to capture the photogrammetric images through the glass allowing the discrete measurement and image processing of the deformation patterns of the pipe conduit during the pipe installation and incremental surcharge loading. Vertical loads were applied in increments of 10150 kPa using air pressure membranes. Electric resistant strain gauges measured the bending moments of the pipe walls under vertical surcharge loadings. For each loading step, the vertical deformation of the pipe crown was also measured using linear position transducers. According to the test results, it is understood that the installation technique and backfill relative density have an important effect on circumferential strains, performance, and deformation characteristics of HDPE pipes. It was also observed that close-range image processing is a very simple and appropriate method for measuring three-dimensional pipe deformations under various conditions.
Keywords: Soil-Pipe Interaction; Laboratory Soil Box Test; Close-Range Photogrammetry; Engineering; Mechanics; Materials Science